Digital image colorimetry for determination of sulfonamides in water - Paulo Jorge Teixeira Silva (2017)
Antimicrobial agents are considered emerging pollutants in water, because of their potential to accelerate spread of bacterial resistance genes, and due to their harmful effect to ecosystem through death or inhibition of natural microbiota. Sulfonamides (SAs) are an important antimicrobial group and it is widely used in both human and veterinary medicine. Studies have demonstrated that SAs are very mobile and highly available in soil with no bioaccumulation. Furthermore, these compounds seem to be quite resistant to biodegradation in surface water which can benefit contamination of aquatic environment. Thus, monitoring of SAs levels in water are very important to determine their aquatic risk assessment. Several methods for determination of SAs in water have been developed. Most of them are based on the coupling of high-performance liquid chromatography (LC) and mass spectrometry (MS). LC-MS is widely used due to their high sensitivity and specificity; however, this approach is very expensive and does not allow in situ analysis. Hence, development of field deployable screening methods is required. Methods based on digital image colorimetry have been broadly applied for point-of-care tests, forensic analysis and environmental monitoring. The digital image based methods are very promising as field screening techniques because they are fast, low cost, portable and easy handling methodologies.